PEREMPUAN DAN INTERNET DALAM PENINGKATAN EKONOMI KELUARGA - Susri Adeni; Sudani Herman; Dedi Supriyadi (Universitas Bengkulu, 2017)
In addressing the problem of poverty, the media also has a very important role. Inaddition, with media, especially the internet, we can find out information about theweather and the sea and fishing information globally accessible. Further explained thatthe resources of this example is FIGIS (fisheries global information system) that provides arange of statistical information such as fisheries, fish distribution maps by species, issueand topic of the actual fisheries, aquaculture, marine fisheries, and fishing technology. Thedata is available anytime and anywhere needed. Based on the background is exactly theservice activities based on this urgent research to be conducted. The activity goal is toprovide knowledge for women and families of fishermen on the media, especially theInternet and equip the women and families of fishermen to learn new media like theinternet. The target audience of the utilization of the internet is for girls and coastal fishingfamilies who live in the city of Bengkulu Malabero coastal areas totaling 10 people whohave a product that can be sold in the market. The activities are lectures, discussions andsimulations use the internet with the ultimate goal the establishment of a blog that can beused to sell their products.Keywords: Internet, women, economics, blogs, information